Developing Communicative Speaking Tasks For The Eleventh Grade Students Of SMAN 1 Losarang - ROPINI SUJI (UNISAedu : Jurnal Ilmiah Ilmu Pendidikan, 2021)
The objective of this study is todevelop communicative speaking tasks for the eleventh grade students at SMA Negeri 1 Losarang Indramayu . This study isto overcome one of the problems related to the limitation of the speaking tasks for students. The nature of this study is a Research and Development (R&D) study. The steps of the study were conducting needs analysis, selecting the topics and objectives ofthe materials, writing the course grid, designing the materials (first draft), getting expert judgment, and writing the final draft. This study involved 37 eleventh grade students and the teacher of SMA Negeri 1 Losarang Indramayu as the research subjects. The data were obtained by administering questionnaires and observations. The results of the needs analysis questionnaires were analyzed using percentage and the expert judgment questionnaires were analyzed using descriptive statistic and frequencies. There were two experts involved to review and evaluate the materials. There were 13 tasks in each unit that were organized into Warming-up, Main activity, Evaluation, Reflection, and Summary. Each unit also provided language function, grammar, and vocabulary sections. Pictures, dialogues, and questions were the preferred input texts in each unit. The activities in each unit were answering the questions based on the picture, completing the survey sheet, practicing the dialogue, making a dialogue by using provided topic, and making a dialogue using free topics. The setting for the materials was in pairs and groups.The finding of this study showed that the developed materials are appropriate based on the results of expert judgment questionnaire. It was proved by the mean value of 3 of overall items.